The flexibility of a homeodomain transcription factor heterodimer and its allosteric regulation by DNA binding. (25th July 2016) - Mathiasen, Lisa; Valentini, Erica; Boivin, Stephane; Cattaneo, Angela; Blasi, Francesco; Svergun, Dmitri I.; Bruckmann, Chiara
Abstract : Transcription factors are known to modify the DNA that they bind. However, DNA can also serve as an allosteric ligand whose binding modifies the conformation of transcriptional regulators. Here, we describe how heterodimer PBX1:PREP1, formed by proteins playing major roles in embryonic development and tumorigenesis, undergoes an allosteric transition upon DNA binding. We demonstrate through a number of biochemical and biophysical methods that PBX1:PREP1 exhibits a structural change upon DNA binding. Small‐angle X‐ray scattering (SAXS), circular dichroism (CD), isothermal titration calorimetry (ITC), and limited proteolysis demonstrate a different shape, α‐helical content, thermodynamic behavior, and solution environment of the holo‐complex (with DNA) compared to the apo‐complex (without DNA). Given that PBX1 as such does not have a defined DNA selectivity, structural changes upon DNA binding become major factors in the function of the PBX1:PREP1 complex. The observed changes are mapped at both the amino‐ and carboxy‐terminal regions of the two proteins thereby providing important insights to determine how PBX1:PREP1 dimer functions. Database: Small‐angle scattering data are available in SASBDB under accession numbers SASDAP7, SASDAQ7, and SASDAR7. Abstract : Transcription factors can modify the shape of DNA; however, DNA can also serve as an allosteric ligand that changes the conformation of transcriptional regulators. We demonstrate through a number of biochemical and biophysical methods that the heterodimer PBX1:PREP1, that plays major roles in embryonic development and tumorigenesis, exhibits a structural change upon DNA binding. These changes provide important insights to determine how PBX1:PREP1 heterodimer functions.